HUBUNGAN CARA BELAJAR DENGAN PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN PKn PADA SISWA KELAS X SMA NEGERI 1 BANJARMASIN - Tiara Ernita, Fatimah, Rabiatul Adawiah (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2016)
Tiara Ernita, 2013. Correlation between Students’ Learning Style and Students’ Learning Achievement at the Tenth Grade Students of SMA Negeri 1 Banjarmasin. Sarjana’s Thesis. Civic Education Department, Social Science, Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin. The first advisor: Fatimah, the second advisor: Rabiatul Adawiah. Learning style is a key factor which determines the success of learning. Each student certainly has different learning style from one another. The level of understanding and mastery on lesson material are influenced by the students’ learning style. This research aims to analyze the students’ learning style at home, to analyze the students’ learning achievement, and to analyze the correlation between the students’ learning style and the students’ learning achievement in civic education lesson at the tenth-grade students of SMA Negeri 1 Banjarmasin. This research uses quantitative approach with sampling technique which utilizes the table of Krejcie and Morgan. The sample is obtained randomly by using lottery. Techniques of data collection are questionnaire, interview, observation, documentation, and also objective and subjective test both in written form. Analyses used on the research result are descriptive analysis and testing of Product Moment correlation.The finding of this research shows that the students’ learning style has significant correlation with their learning achievement. It is indicated on the testing result of Product Moment correlation namely 0,879. After the value was adjusted to table of r value interpretation, 0,879 value is in the interval coefficient between 0,80 to 1,000. It is interpreted as very strong category.Based on the finding of this research, it is suggested that the students should employ effective learning style. Therefore, it is necessary to improve the awareness of the importance of good learning style, so the leanring achievement can be improved. It is also expected that the teachers can motivate the students to have effective learning style, both at home and at school. In addition, it is also suggested that the school fulfil the conditions which can fully support the students’ learning achievement. In this case, the school should create learning atmosphere that can increase the students’ learning motivation, so they can actively engaged in learning process in the classroom. For the Civic Education department, this research can add the theory about the correlation between students’ learning style and the students’ learning achievement. For the researcher herself, this research can add knowledge about students’ learning style, so that the researcher can implement the findings of this research when executing the teacher profession later. Keywords: learning style, students’ learning achievement